Dynamic compressive properties of novel lightweight ambient-cured EPS geopolymer composite - Li, Z.; Chen, Wensu; Hao, Hong; Khan, M.Z.N.; Pham, Thong (ELSEVIER SCI LTD, 2021)
Geopolymer as eco-friendly and alternative cementitious material has been intensively investigated. In a previous study, Expanded Polystyrene (EPS) of volume fractions of 10%, 20% and 30% was mixed into the ambient-cured plain geopolymer mortar (GM) to form lightweight geopolymer composite (LGC). The static mechanical properties were tested and reported. The developed LGC can be used in various applications such as road barriers, tunnel cushions and lightweight building products i.e. bricks and panels, which could be subjected to dynamic loads such as impact or blast. Therefore, its dynamic properties need to be investigated. In this study, dynamic compressive properties of LGC were investigated by using Ø100-mm split Hopkinson pressure bar (SHPB). The failure processes and the failure modes of plain GM and LGC specimens with various EPS contents under different strain rates, as well as the stress–strain curves and the energy absorption capacity were compared. The strain rate effect on the dynamic compressive strength, axial strain at peak stress and normalized energy absorption capacities were compared and analysed. The test results showed that dynamic compressive properties and energy absorption capacity of LGC with more EPS contents were more sensitive to the strain rate. Based on the testing results, the empirical formulae of dynamic increase factor of compressive strength and energy absorption versus strain rate were proposed.